The Role of the Metabolism of Zinc and Manganese Ions in Human Cancerogenesis - Julian Markovich Rozenberg; Margarita Kamynina; Maksim Sorokin; Marianna Zolotovskaia; Elena Koroleva; Kristina Kremenchutckaya; Alexander Gudkov; Anton Buzdin; Nicolas Borisov (Biomedicines, 2022)
Metal ion homeostasis is fundamental for life. Specifically, transition metals iron, manganese and zinc play a pivotal role in mitochondrial metabolism and energy generation, anti-oxidation defense, transcriptional regulation and the immune response. The misregulation of expression or mutations in ion carriers and the corresponding changes in Mn2+ and Zn2+ levels suggest that these ions play a pivotal role in cancer progression. Moreover, coordinated changes in Mn2+ and Zn2+ ion carriers have been detected, suggesting that particular mechanisms influenced by both ions might be required for the growth of cancer cells, metastasis and immune evasion. Here, we present a review of zinc and manganese pathophysiology suggesting that these ions might cooperatively regulate cancerogenesis. Zn and Mn effects converge on mitochondria-induced apoptosis, transcriptional regulation and the cGAS-STING signaling pathway, mediating the immune response. Both Zn and Mn influence cancer progression and impact treatment efficacy in animal models and clinical trials. We predict that novel strategies targeting the regulation of both Zn and Mn in cancer will complement current therapeutic strategies.